2015
DOI: 10.1016/j.ress.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Optimum maintenance strategy under uncertainty in the lifetime distribution

Abstract: The problem of determining the optimal maintenance strategy for a machine given its lifetime distribution has been studied extensively. Solutions to this problem are outlined in the academic literature, prescribed in professional handbooks, implemented in reliability engineering software systems and widely used in practice. These solutions typically assume that the lifetime distribution and its parameter values are known with certainty, although this is usually not the case in practice. In this paper we study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Recent literature in aircraft maintenance safety tends to accept that deviations, uncertainties and surprises are inherent and to a large extent inevitable in maintenance operations [10,23,4]. In the process of avionics systems equipment maintenance, some judgments from maintenance experts or engineers may not be (fully) compatible due to lack of knowledge of the actual use and maintenance of the equipment.…”
Section: Finally a Specific Example Of Decision Of Maintenance Stratmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature in aircraft maintenance safety tends to accept that deviations, uncertainties and surprises are inherent and to a large extent inevitable in maintenance operations [10,23,4]. In the process of avionics systems equipment maintenance, some judgments from maintenance experts or engineers may not be (fully) compatible due to lack of knowledge of the actual use and maintenance of the equipment.…”
Section: Finally a Specific Example Of Decision Of Maintenance Stratmentioning
confidence: 99%
“…where, 1 c is indicator of system safety, 2 c is Reliability, 3 c is Maintainability, 4 c is maintenance economy, 5 c is availability.…”
Section: Case Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Coolen and his coauthors [9,10] showed that this assumption impacts clearly the optimal replacement age and its cost per unit of time when the equipments undergo an age replacement policy (ARP). Recently in [11], de Jonge et al pointed out also the weakness of the assumption on knowing of the equipment lifetime distribution and proposed a parametric modeling of ARP for new equipment with an uncertainty on the parameters of the equipment lifetime distribution. In this work, de Jonge and his coauthors used Bayesian approach to model the uncertainty on the parameters and figured out that this uncertainty has effects on the optimal policy (age and cost) under ARP.…”
Section: Introductionmentioning
confidence: 99%
“…An important element of accurate modelling of the system, is the decision of which probability distributions to use for the degradation rates of the components. This has been shown to have a major impact on the optimal maintenance policy and the total maintenance cost [dJKTT15]. FMTs support arbitrary probability distributions, allowing modellers to choose the most appropriate one, or experiment with different distributions to examine how much the choice impacts the results.…”
Section: Example 2 Figure 13 Shows Part Of a Fault Maintenance Tree mentioning
confidence: 99%